Testing crossover effects in an actor–partner interdependence model among Chinese dual‐earner couples. (26th April 2014) - Liu, Huimin; Cheung, Fanny M.
<x xml:space="preserve">Abstract</x> The purpose of the present study is to examine the crossover effects from one partner's work–family interface (work–family conflict [WFC] and work–family enrichment [WFE]) to the other partner's four outcomes (psychological strain, life satisfaction, marital satisfaction and job satisfaction) in a sample of Chinese dual‐earner couples. Married couples (N = 361) completed a battery of questionnaires, including the work–family interface scale, the psychological strain scale, the life, marital, as well as job satisfaction scale. Results from the actor–partner interdependence model (APIM) analyses showed that wives' WFE was negatively associated with husbands' psychological strain, and positively associated with husbands' life, marital and job satisfaction. Furthermore, husbands' WFC was negatively related to wives' marital satisfaction, whereas husbands' WFE was positively related to wives' marital satisfaction. Theoretical and practical implications were discussed, and future research directions were provided.